TGR5, Not Only a Metabolic Regulator - Guo, Cong; Chen, Wei-Dong; Wang, Yan-Dong (Frontiers in Physiology, 2016)
G-protein-coupled bile acid receptor, Gpbar1 (TGR5), is a member of G-protein-coupled receptor (GPCR) superfamily. High levels of TGR5 mRNA were detected in several tissues such as small intestine, stomach, liver, lung, especially in placenta and spleen. TGR5 is not only the receptor for bile acids, but also the receptor for multiple selective synthetic agonists such as 6α-ethyl-23(S)-methyl-cholic acid (6-EMCA, INT-777) and a series of 4-benzofuranyloxynicotinamde derivatives to regulate different signaling pathways such as nuclear factor κB (NF-κB), AKT and extracellular signal-regulated kinases (ERK). TGR5, as a metabolic regulator, is involved in energy homeostasis, bile acid homeostasis, as well as glucose metabolism. More recently, our group and others have extended the functions of TGR5 to more than metabolic regulation, which include inflammatory response, cancer and liver regeneration. These findings highlight TGR5 as a potential drug target for different diseases. This review summarizes the basic information of TGR5 and its new functions.